The money laundry: regulating criminal finance in the global economy - Sharman, Jason C. (Cornell studies in political economy, 2011)
Introduction : policy diffusion and anti-money laundering -- Money laundering and anti-money laundering -- An indirect test of effectiveness -- A direct test of effectiveness -- Blacklisting -- Socialization and competition -- Conclusions : implications for scholarship and policy